2012
DOI: 10.1111/j.1471-6712.2012.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

The space of togetherness – a caring encounter

Abstract: Encounters in relation to the nurse-patient relationship are often discussed within nursing and caring literature without a reflection on the actual meaning of the concept. Assuming that an encounter is essential for nursing care, this article seeks to create a deeper understanding of the concept through a hermeneutic approach to texts by the philosophers Buber and Marcel. Presence, recognition, availability and mutuality seem to be essential prerequisites for an encounter. As these prerequisites are fulfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 8 publications
(9 reference statements)
2
40
0
Order By: Relevance
“…Given such findings, it is reasonable to infer that if patients in general cause named difficulties, dealing with patients with mental ill‐health must be even more challenging. Holopainen et al identified and listed four factors – presence, recognition, availability and mutuality – as required components for ‘caring encounters’ to take place. In the context of the previously mentioned obstacle ‘lack of time’, the authors discuss whether caring encounters can emerge in the time‐constrained and technologically driven environments of modern nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Given such findings, it is reasonable to infer that if patients in general cause named difficulties, dealing with patients with mental ill‐health must be even more challenging. Holopainen et al identified and listed four factors – presence, recognition, availability and mutuality – as required components for ‘caring encounters’ to take place. In the context of the previously mentioned obstacle ‘lack of time’, the authors discuss whether caring encounters can emerge in the time‐constrained and technologically driven environments of modern nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Peplau () suggest that powerlessness is a part of being affected as a patient but powerlessness might decrease when acknowledged in a relationship with a nurse. In the presence of the clinicians, the SOs' experience togetherness and mutuality (Holopainen et al , ). In this relationship the SOs might share their struggle for the affected person with the clinicians.…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…The NPR has been the focus of many studies and the large volume of literature devoted to this relationship highlights its importance (Holopainen, Kas en, & Nystr€ om, 2014;Kas en, 1996;Morse, 1991;Peplau, 2004). The essence of the NPR seems difficult to conceptualize.…”
Section: Introductionmentioning
confidence: 99%